2019
DOI: 10.1002/aur.2230
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Motor Difficulties in Autism Spectrum Disorder: Analysis of a Population‐Based Cohort

Abstract: Motor impairment is not currently included in the diagnostic criteria or evaluation of autism. This reflects the lack of large‐scale studies demonstrating its prominence to advocate for change. We examined the prevalence of motor difficulties at the time of diagnosis in a large sample of children with autism utilizing standardized assessment, and the relationship between motor difficulties, core autism symptomology, and other prominent clinical features. Vineland Adaptive Behavior Scales were administered to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
115
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 38 publications
13
115
1
3
Order By: Relevance
“…The distribution of the subscale quotients of the GMDS across different age groups suggested that locomotor skills tend to decrease in line with age at diagnosis. This pattern is consistent with findings from previous studies that motor difficulties become more pronounced with age (Landa and Garrett-Mayer, 2006;Lloyd et al, 2013;Licari et al, 2020). The transition from infancy to preschool child requires the acquisition of increasingly complex movement skills through increases in muscle strength, coordination, and stability (Licari et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The distribution of the subscale quotients of the GMDS across different age groups suggested that locomotor skills tend to decrease in line with age at diagnosis. This pattern is consistent with findings from previous studies that motor difficulties become more pronounced with age (Landa and Garrett-Mayer, 2006;Lloyd et al, 2013;Licari et al, 2020). The transition from infancy to preschool child requires the acquisition of increasingly complex movement skills through increases in muscle strength, coordination, and stability (Licari et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…This pattern is consistent with findings from previous studies that motor difficulties become more pronounced with age (Landa and Garrett-Mayer, 2006;Lloyd et al, 2013;Licari et al, 2020). The transition from infancy to preschool child requires the acquisition of increasingly complex movement skills through increases in muscle strength, coordination, and stability (Licari et al, 2020). If a child has challenges in acquiring simple movement skills, it will be more difficult to acquire complex movement skills during subsequent development stages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lack of a strong repetitive behavior phenotype or social impairment illustrates the challenge of modeling ASD in mice using the available behavioral paradigms. Although at least one study on mouse models of ASD has considered increased rotarod performance to resemble a repetitive behavior [Rothwell et al, 2014], humans with ASD tend to show motor impairments, rather than improvements in motor function [Licari et al, 2020]. It is therefore surprising that our model showed improvements in motor function and these findings directly contradict what has been reported in several other mouse models of ASD .…”
Section: Discussioncontrasting
confidence: 66%
“…Restricted repetitive behaviors, prevalent in ASD and other neurodevelopmental conditions, include stereotypy, rituals, and compulsions and have been reported to develop, in part, due to decreased indirect pathway activity in a mouse model (Tanimura et al, 2011). Recently, a large study of 2,084 children with ASD ≤6 years old measuring motor domain criteria from Vineland tests reported that 35% had significant motor difficulties with another 44% classified as moderately low skilled and included motor stereotypies (hand flapping, spinning, body rocking), and non-verbal behaviors such as use of body postures and gestures (Licari et al, 2020). While many components in the brain contribute to a variety of these motor functions, MSNs in the dorsal striatum are considered to play a prominent role.…”
Section: Implications Of Dysfunction Of the Indirect Pathwaymentioning
confidence: 99%